COMPARATIVE ANALYSIS OF MELANOMA DEVELOPMENT AND PREVENTION OF ULTRAVIOLET RADIATION EXPOSURE IN UKRAINE AND ITALY - Hryhorian, O.V.; Litovchenko, O.L.; Zavgorodnia, N.I. (World of Medicine and Biology, 2025)
The most common cause of melanoma is exposure to ultraviolet radiation due to ultraviolet mutagenesis. The purpose of the study was to highlight and make a comparative analysis of the incidence of melanoma in Ukraine and Italy, taking into account different levels of insolation, and to assess the effectiveness of existing preventive measures to protect against ultraviolet radiation. A search, systematic review, and meta-analysis of publications were conducted using scientific literature databases, including MEDLINE, Scopus®, ResearchGate, PubMed, and Google Scholar. The comparative analysis of melanoma incidence in Ukraine and Italy revealed a clear upward trend in both countries. However, even with moderate UV index levels in Ukraine, an increase in diagnosed melanoma cases has been observed, emphasizing the relevance of identifying and preventing the impact of UV radiation. At the same time, studies indicate insufficient adherence to individual sun protection measures among both adults and children in Italy, which is a significant risk factor for melanoma development.
Keywords: ultraviolet radiation; risk factors; melanoma; prevention; Ukraine; Italy